Unbundling the Effects of College on First-Job Search: Returns to Majors, Minors, and Extracurriculars - Jaime Arellano-Bover; Carolina Bussotti; John M. Nunley; R. Alan Seals (Institute of Labor Economics (IZA), 2024)
We analyze the initial job-market matching of new US college graduates with a largescale audit study conducted during 2016 and 2017, in which 36,880 résumés of college seniors were submitted to online job postings for business-related positions. We simulate the experience of US college students by incorporating variation in curricular and extracurricular activities. Our analysis reveals significant variation in callback rate returns to majors, with Biology and Economics majors receiving the highest rate, particularly in occupations involving high intensity of analytical and interpersonal skills. However, minors in History and Mathematics have precisely estimated zero effects on callback rates. Internship experiences that are social skills-oriented positively influence callbacks, yet this is not the case for analytical internships. Study abroad experiences enhance callback rates, predominantly in high interpersonal skill-intensive occupations. Listing both programming and data analysis skills significantly boosts callback rates. Our study provides a comprehensive characterization of which features of the college experience are more and less valuable during the high-stakes, first-job matching process.
Keywords: I26; J23; J24; 330; returns to college; first job; majors; minors; audit study